RISING RESISTANCE IN UROPATHOGENS WITH AN INDICATION OF NITROFURANTOIN MIC CREEP - Hasan, Azra S; Richa Garg,; Sowmya nasimuddin,; Sneha Dey ,; Ayan Das ,; Syed Md. Moosi Raza Ali ,; Sumit Rai ,; Dalip K. Kakru, (Journal of Ayub Medical College Abbottabad, 2023)
Background: The irrational use of antibiotics has led to the emergence of multi drug resistant pathogens. The phenomenon of MIC creeps occurs when organisms start showing raised MIC but within susceptible range giving an indication of the prevalence of rise in resistant pathogens in an area Methods: A cross sectional study in a large tertiary care hospital in North India to observe the susceptibility pattern among uropathogens and the possibility of MIC creeps. The Antimicrobial Susceptibility Testing (AST) and Minimum Inhibitory Concentration (MIC) were conducted by Vitek Compact 2. The identification of Extended Spectrum Beta Lactamase (ESBL) producers and Carbapenem Resistant Enterobacteriaceae (CRE) among Escherichia coli were noted. The MIC 50 and MIC 90 for Nitrofurantoin, the most widely used antibiotic for lower UTI, was calculated to investigate the phenomenon of MIC creep. Results: In our study, a total of 2522 urine samples were analyzed:1538 (61%) were positive with the commonest isolate being E. coli (n=736, 47.8%) followed by Klebsiella spp. (n=178, 11%). Less than 10% of resistance was observed for Fosfomycin, Amikacin, Nitrofurantoin, Imipenem, Meropenem and Colistin. ESBL producers and CRE E. coli were 528 (72% of 736) and 79 (11% of 736) respectively. Overall, 119/736 samples had an MIC ‰¥128. Amongst the ESBL producers, 96/528 had MIC ‰¥ 128 and amongst the CRE, 13/79 had MIC ‰¥ 128. Discussion: E. coli can be used to reflect the trends in development of resistance. In the current study, it was observed that E. coli showed a reduced susceptibility for Nitrofurantoin indicated by a creeping increase in MIC albeit within normal range. Conclusion: Trends in rising MIC should alert prescribers to use drugs such as Nitrofurantoin judiciously. Antimicrobial stewardship practices should be strongly implemented in hospitals to curb rising resistance and obtain better treatment outcomes for patients with infectious diseases.